Work On the Word in German Lessons at The University. Features Of the Lexical Approaches - Zaripov Jamshid (Genius Journals, 2022)
The article is devoted to the lexical approach to teaching foreign languages, which allows you to put the student at the center of the educational process and develop his communication skills. The growing interest in the lexical aspect has recently been determined by the transition from grammar to the student's vocabulary, the formation of which is the main goal of learning a foreign language.
Keywords: Lexical approach; lexical materials; development of lexical units; personal aspects of learning,